Trophic Magnification of Legacy (PCB, DDT and Hg) and Emerging Pollutants (PFAS) in the Fish Community of a Small Protected Southern Alpine Lake (Lake Mergozzo, Northern Italy) - Michela Mazzoni (Water, 2020)
The biomagnification of mercury, polychlorobiphenyls (PCBs), dichlorodiphenyltrichloroethane and its metabolites (DDTs) and perfluoroalkyl acids substances (PFASs) was evaluated in the trophic web of Lake Mergozzo, a small and deep Italian subalpine lake, which has been chosen because it is a protected environment, and discharges into the lake are mostly avoided. Carbon source and relative trophic levels were calculated by using 13C and 15N stable isotopes, respectively, and trophic magnification factors (TMFs) were derived. Zooplankton and thirteen species of fish were collected and analyzed, and the results showed the elevated level of biota contamination from both legacy and emerging pollutants, even if direct discharges were avoided. Concentrations in biota, expressed as sums of compounds, ranged from 0.4 to 60 µg kg−1 wet weight (ww) for PFASs, from 16 to 1.3 104 µg kg−1 lipid content (lw) for DDTs, from 17 to 1.5 104 µg kg−1 lw for PCBs and from 20.0 to 501 µg kg−1 ww for mercury (Hg). TMFs of this deep, cold lake, with a prevalent pelagic trophic chain, were high and clearly indicated fish biomagnification, except for PFAS. The biomagnification capability of PFAS in a fish-only food web was discussed by using the biomagnification of Hg as a benchmark for assessing their bioaccumulation potential.